2013
DOI: 10.1186/1556-276x-8-25
|View full text |Cite
|
Sign up to set email alerts
|

p-Type hydrogen sensing with Al- and V-doped TiO2 nanostructures

Abstract: Doping with other elements is one of the efficient ways to modify the physical and chemical properties of TiO2 nanomaterials. In the present work, anatase TiO2 nanofilms doped with Al and V elements were fabricated through anodic oxidation of Ti6Al4V alloy and further annealing treatment. Hydrogen sensing behavior of the crystallized Ti-Al-V-O nanofilms at various working temperatures was investigated through exposure to 1,000 ppm H2. Different from n-type hydrogen sensing characteristics of undoped TiO2 nanot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 41 publications
(38 reference statements)
0
26
0
Order By: Relevance
“…TiO 2 -based mixed oxides have also been reported to show p-type semiconductivity and good visible transparency for interesting TSO applications. For example, Li et al [160] prepared Ti-Al-V-O oxide nanofilms with anatase structures by anodization and annealing. Anatase TiO 2 nanofilms doped with Al and V were fabricated through anodic oxidation of Ti6Al4 V alloy and annealing treatment.…”
Section: Spray Pyrolysismentioning
confidence: 99%
“…TiO 2 -based mixed oxides have also been reported to show p-type semiconductivity and good visible transparency for interesting TSO applications. For example, Li et al [160] prepared Ti-Al-V-O oxide nanofilms with anatase structures by anodization and annealing. Anatase TiO 2 nanofilms doped with Al and V were fabricated through anodic oxidation of Ti6Al4 V alloy and annealing treatment.…”
Section: Spray Pyrolysismentioning
confidence: 99%
“…The incorporation of Al and V in TiO 2 tubular arrays also changes their response mechanism towards hydrogen. The conductance of the Al-V-TiO 2 structure decreased upon exposure to a hydrogen-containing atmosphere [ 126 ]. Furthermore, it has been reported that the presence of Cr in the TiO 2 lattice leads to the change of charge transfer mechanism for a high concentration of NO 2 (50 ppm) at the elevated operating temperature (500 °C).…”
Section: Sensing Properties Of Tiomentioning
confidence: 99%
“…The materials’ conductance increased showing p-type response [ 123 ]. Pure TiO 2 nanotubes obtained under the same conditions, showed n-type response [ 123 , 126 ]. The aforementioned investigations showing that at certain temperatures, depending on the gas type and concentration, the response mechanism of doped and mixed TiO 2 nanotubes may change.…”
Section: Sensing Properties Of Tiomentioning
confidence: 99%
“…As far as Cr-doped TiO 2 is concerned, the optimum temperature for sensing properties has been limited with 500 • C while the Al-doped TiO 2 detects NO 2 at 600 • C but the sensitivity is low and the signal converts to p-type at 800 • C (Saruhan et al, 2013;Gönüllü et al, 2015). Several other papers discuss the relation and reasons between the nature of the electronic structure and the sensing characteristics of the oxide materials (Wisitsoraat et al, 2009;Zhaohui et al, 2013;Gönüllü et al, 2015) and report that the enhancement of the sensing performance can directly be controlled by adjustment of the electronic structure to p-type at the semi-conducting oxide sensing layer.…”
Section: Introductionmentioning
confidence: 99%